Screening Criteria for Amyloidosis Biopsy Testing during Carpal Tunnel Release in Community Hospitals: Evaluation and Application - Sacchetti, Michael E.; Desai, Shivam; Hunt, Bradley; Keane, Charles; Hoque, Asef; Bailey, Beth; Zacharek, Anthony (Journal of Wrist Surgery, 2025)
Carpal tunnel syndrome (CTS) is a common disorder caused by median nerve compression. Current research has explored the relationship between CTS and cardiac amyloidosis, which can lead to poor health outcomes, highlighting the need for screening guidelines. Although recommendations exist for when to biopsy during carpal tunnel release (CTR), studies have primarily focused on urban or academic centers. This study evaluates these recommendations in a community hospital setting serving a predominantly rural population.This retrospective study assessed risk factor based screening recommendations for intraoperative tenosynovial biopsy during open CTR. All procedures were performed by a single plastic surgeon. Positive Congo red staining samples were sent to the Mayo Clinic for confirmatory testing. Positive and negative amyloidosis cases were compared, with analyses stratified based on associated risk factors.The study included 105 patients (47.6% female) with a median age of 66.0 years old. Of these, 9.5% (n = 10) tested positive for amyloidosis. The median age of those who tested positive for amyloidosis was 81.5 years, compared with 65.0 years in those who tested negative. Of the 10 positive cases for amyloidosis, 7 patients had a history of chronic kidney disease (CKD), and 6 patients tested positive for the ATTR subtype.With an overall amyloidosis positivity rate of 9.5%, this falls within range of previously reported positivity rates. Given the community hospital setting, ensuring follow-up is crucial, especially to determine if a positive result warrants amyloidosis treatment. Strong collaboration between hand surgeons and specialists is essential for coordinated local or tertiary care follow-up.
Keywords: amyloidosis; carpal tunnel syndrome; carpal tunnel release; screening; community hospital